2019
DOI: 10.1038/s41419-019-1883-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of pyroptosis in cancer: pro-cancer or pro-“host”?

Abstract: Programmed cell death (PCD) refers to the way in which cells die depending on specific genes encoding signals or activities. Apoptosis, autophagy, and pyroptosis are all mechanisms of PCD. Among these mechanisms, pyroptosis is mediated by the gasdermin family, accompanied by inflammatory and immune responses. The relationship between pyroptosis and cancer is complex, and the effects of pyroptosis on cancer vary in different tissues and genetic backgrounds. On one hand, pyroptosis can inhibit the occurrence and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
695
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 645 publications
(702 citation statements)
references
References 125 publications
(164 reference statements)
6
695
0
1
Order By: Relevance
“…GSDMC functioned as an oncogene, enhancing cell proliferation and tumorigenesis in lung adenocarcinoma and colorectal carcinogenesis ( Miguchi et al, 2016 ; Wei et al, 2020 ). It presented high in malignant melanoma but undetectable in normal epithelial cells, which might be associated with the metastasis of cells ( Xia et al, 2019 ). CSTA, one of the tumor suppressors, had the anti-apoptotic effect and maintaining cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…GSDMC functioned as an oncogene, enhancing cell proliferation and tumorigenesis in lung adenocarcinoma and colorectal carcinogenesis ( Miguchi et al, 2016 ; Wei et al, 2020 ). It presented high in malignant melanoma but undetectable in normal epithelial cells, which might be associated with the metastasis of cells ( Xia et al, 2019 ). CSTA, one of the tumor suppressors, had the anti-apoptotic effect and maintaining cell-cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen from the above, GSDME-mediated pyroptosis can kill tumor cells. Some scholars have suggested that during the treatment of malignant tumors, appropriate chemotherapeutic drugs can be selected according to the expression of GSDME, thereby increasing the sensitivity to chemotherapeutic drugs, enhancing the anti-tumor immunity and reducing drug resistance 74 . However, some scholars also proposed that the high expression of GSDME would enhance the side effects of chemotherapy.…”
Section: High-level Gsdme Increased the Side Effect Of Chemotherapymentioning
confidence: 99%
“…When bleomycin was administered to mice, WT mice developed more severe lung injury and inflammation than GSDME −/− mice. GSDME-mediated pyroptosis can kill normal cells and increase the adverse effect of chemotherapy 5 , 36 , 74 . So, how to avoid the side effects of GSDME in the treatment of cancer is the focus of the next step.…”
Section: High-level Gsdme Increased the Side Effect Of Chemotherapymentioning
confidence: 99%
“…The relationship between pyroptosis and cancer is context dependent and complex. Pyroptosis may be capable of being either pro- or anti-cancer [ 71 ]. On one hand, the release of inflammatory mediators and induction of hyperactive signaling pathways may promote tumorigenesis and lead to drug resistance.…”
Section: Resultsmentioning
confidence: 99%